2022
DOI: 10.1016/j.vaccine.2022.02.047
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the E484K mutation of SARS-CoV-2 on the neutralizing activity of antibodies from BNT162b2 vaccinated individuals

Abstract: The reduced vaccine efficacy against the SARS-CoV-2 variant lineage B. 1.351 (beta variant) containing the E484K and N501Y mutations is well known. The E484K mutation in SARS-CoV-2 is thought to be responsible for weakened humoral immunity. Vaccine efficacy against the R.1 lineage, which contains the E484K mutation but not the N501Y mutation, is uncertain. Serum samples were collected from 100 healthy Japanese participants three weeks after receiving the second dose of the BNT162b2 vaccine, and serum neutraliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“… 21 , 22 , 23 COVID‐19 decreased mortality rates in February and March 2021 despite the emergence of Alpha, Beta, and Gamma variants, compared to December 2020 and January 2021, which may be attributed to the national lockdown implemented by the government in late December 2020, vaccination of the healthcare worker and a few elderly people and probably the herd immunity developed in a relative proportion of the individuals exposed to the infection. Since it has been demonstrated that SARS‐CoV‐2 variants may be capable of escaping from neutralizing antibodies and decreasing the antibody efficacy, 24 identifying the mutants would help quick implementation of control measures to reduce the consequence of the disease. 25 Although the sensitivity of the RT‐PCR test is not 100% and could be affected by the type of sampling and the items and equipment used, it has remained the mainstay of COVID‐19 diagnosis since the beginning of the outbreak.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 , 23 COVID‐19 decreased mortality rates in February and March 2021 despite the emergence of Alpha, Beta, and Gamma variants, compared to December 2020 and January 2021, which may be attributed to the national lockdown implemented by the government in late December 2020, vaccination of the healthcare worker and a few elderly people and probably the herd immunity developed in a relative proportion of the individuals exposed to the infection. Since it has been demonstrated that SARS‐CoV‐2 variants may be capable of escaping from neutralizing antibodies and decreasing the antibody efficacy, 24 identifying the mutants would help quick implementation of control measures to reduce the consequence of the disease. 25 Although the sensitivity of the RT‐PCR test is not 100% and could be affected by the type of sampling and the items and equipment used, it has remained the mainstay of COVID‐19 diagnosis since the beginning of the outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the relationships between neutralizing antibody titers against the Omicron variant (NA-Omicron) and for RBD-IgG, neutralizing antibody titers in the serum samples collected 3 weeks after the third dose were measured using Omicron (B.1.1.529) variant strains clinically isolated at Keio University Hospital. The detailed methods are described in a previous report [ 6 ].…”
Section: Participants and Methodsmentioning
confidence: 99%
“…The SARS-CoV-2 wild-type strain (original strain) (EPI_ISL_408667) provided by the National Institute of Infectious Diseases (Tokyo, Japan) and Omicron (B.1.1.529) variant strain clinically isolated at Keio University Hospital were prepared for the assay. Mutations in the two virus preparations used for the experiments were validated by whole genome sequencing [ 12 ]. The cells were maintained with Dulbecco’s modified Eagle medium with 5% fetal calf serum.…”
Section: Methodsmentioning
confidence: 99%